A LATE PLEISTOCENE ENDEMIC GENET (CARNIVORA, VIVERRIDAE) FROM AGHIA NAPA, CYPRUS - Theodorou, G. E.; Roussiakìs, S. I.; Athanassiou, A.; Giaourtsakis, I.; Panayides, I. (Bulletin of the Geological Society of Greece, 2007)
The Pleistocene endemic fauna of Cyprus consists mainly of dwarf hippos and elephants, adapted to the insular environment. Among the rare elements of this endemic fauna is a small carnivore, the viverrid Genetta plesictoides, poorly known from scanty material that comes from two localities. Recent excavations in a rockshelter site at the area of Aghia Napa yielded —apart from a rich hippo sample—new skeletal remains (a partial skull and a tibia) of the cypriot genet. The dental morphology shows adaptations towards a more carnivorous diet in relation to the extant Genetta genetta.